A Brief History of Breast Reconstruction and a Discussion of Two Common Autologous Breast Reconstruction Surgeries: The Free Deep Inferior Epigastric Perforator Flap and the Free Transverse Rectus Abdominis Musculocutaneous Flap - Phillips, Timothy J; Williams, Jason (DALHOUSIE MEDICAL JOURNAL, 2011)
Breast cancer has long been recognized as a challenging disease to treat. In the past 100 years the five-year survivalof the disease has increased from a dismal 4-30% up to 87%.1,2 Surgical techniques have advanced from barbaricremoval of the breast in the 15th and 16th century to advanced, highly technical tumour excisions with breastreconstructioninvolving artificial implants or tissues from the patient‘s own body. The Deep Inferior EpigastricPerforator Flap (DIEP) and the Transverse Rectus Abdominis Musculocutaneous (TRAM) Flap are two commonlyused autologous free flap techniques. Evolution of technique has led to both procedures having high success ratesand low complication rates. Whether a DIEP is performed over a TRAM typically depends on surgeon experienceand patient anatomy. Selection of which flap to use and whether there are any clear advantages of DIEP over freeTRAM is an ongoing debate. Common complications for the free TRAM flap are mainly at the abdominal donor sitewhile the DIEP complications are in the flap itself. Current studies suggest that the three most important factors inselecting a flap are patient‘s obesity, patient‘s arterial anatomy at the donor site, and whether a bilateral flap is beingperformed. Ideally, a multi-center study would be performed which examines a wide range of donor site and flapcomplications to determine whether the increased time and risk of performing the DIEP equates to better patientoutcomes compared to the free TRAM. For now, most authors advocate for proper patient selection, along withintra-operative assessment of the patient‘s perforating vessels as the best way to optimize outcomes and avoidcomplications.